2022
DOI: 10.3390/jmse10020235
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Wave Propagation in a Borehole with a Gas Hydrate-Bearing Sediment

Abstract: A knowledge of wave propagation in boreholes with gas hydrate-bearing sediments, a typical three-phase porous medium, is of great significance for better applications of acoustic logging information on the exploitation of gas hydrate. To study the wave propagation in such waveguides based on the Carcione–Leclaire three-phase theory, according to the equations of motion and constitutive relations, a staggered-grid finite-difference time-domain (FDTD) scheme and a real axis integration (RAI) algorithm in a two-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…An example of a gas hydrate-bearing sediment proves that Equation ( 13) can be used to invert the gas hydrate saturation of the reservoir. Figure 2a,b show the borehole waveforms at distances of 2 m and 3 m, which are simulated by the staggered-grid finite-difference timedomain method in our previous work [34]. A rectangular window was used to intercept the flexural wave.…”
Section: The Inversion Methods and Application To Field Datamentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a gas hydrate-bearing sediment proves that Equation ( 13) can be used to invert the gas hydrate saturation of the reservoir. Figure 2a,b show the borehole waveforms at distances of 2 m and 3 m, which are simulated by the staggered-grid finite-difference timedomain method in our previous work [34]. A rectangular window was used to intercept the flexural wave.…”
Section: The Inversion Methods and Application To Field Datamentioning
confidence: 99%
“…The lack of research on the borehole acoustic field of multiphase porous media hampers the effective utilization of guide wave information. The authors of this paper [34] studied the monopole borehole acoustic wavefield of a three-phase porous medium using the staggered-grid finite-difference time-domain (FDTD) scheme and the real axis integration (RAI) algorithm.…”
Section: Of 18mentioning
confidence: 99%
“…The mechanical properties of hydrate sediments are governed by the hydrate distribution in addition to factors such as net confining pressure, saturation, and mid-major stress coefficient [30]. Hydrate in hydrate sediments exists in three main forms [31], as shown in Figure 3: (i) pore-filling (Figure 4a); (ii) acting as a sediment soil skeleton (Figure 4b), and (iii) cemented between soil particles in the form of colloidal material (Figure 4c). Among them, the results of Waite et al [32] and Brugada et al [17] both showed that the pore-filling type has less influence on the mechanical properties of hydrate sediments, and the influence of hydrate distribution factors on the simulation results can be excluded to the maximum extent.…”
Section: Contact Models and Parametersmentioning
confidence: 99%
“…Therefore, the pore-filling-type structure is used in the modeling in this paper. In this paper, the parallel bonding model is chosen to calculate the contact state between particles according to the model of cemented clustered hydrate sediment distribution proposed by Li et al [31], i.e., there is bonding not only between hydrate and hydrate particles, but also between hydrate and soil particles, as shown in Figure 5. Figure In this paper, the parallel bonding model is chosen to calculate the contact state between particles according to the model of cemented clustered hydrate sediment distribution proposed by Li et al [31], i.e., there is bonding not only between hydrate and hydrate particles, but also between hydrate and soil particles, as shown in Figure 5.…”
Section: Contact Models and Parametersmentioning
confidence: 99%